Brain computation as hierarchical abstraction - Ballard, Dana H. (Dana Harry), 1946- (Cambridge, Massachusetts : The MIT Press, 2015)
The vast differences between the brain's neural circuitry and a computer's silicon circuitry might suggest that they have nothing in common. In fact, as Dana Ballard argues in this book, computational tools are essential for understanding brain function. Ballard shows that the hierarchical organisation of the brain has many parallels with the hierarchical organisation of computing; as in silicon computing, the complexities of brain computation can be dramatically simplified when its computation is factored into different levels of abstraction.
Brain computation -- Brain overview -- Neurons and circuits -- Cortical memory -- Programs via reinforcement -- Sensory-motor routines -- Motor routines -- Operating system -- Decision making -- Emotions -- Consciousness.
Includes bibliographical references and index.
Print version record.
Added to collection customer.56279.3
Keywords: Computational neuroscience; Neurobiology; Neural networks (Computer science); Brain -- physiology; Mental Processes -- physiology; Neurobiology; Models, Neurological; Nerve Net -- physiology; Neural Networks, Computer; Neurons -- physiology; Neurosciences informatiques; Neurobiologie; Réseaux neuronaux (Informatique); MEDICAL -- Physiology; SCIENCE -- Life Sciences -- Human Anatomy & Physiology; COMPUTERS -- Data Modeling & Design; Neural networks (Computer science); Computational neuroscience; Neurobiology; NEUROSCIENCE/General; Internet Resources